Associations of Low Vitamin D and Elevated Parathyroid Hormone Concentrations With Bone Mineral Density in Perinatally HIV-Infected Children. (1st September 2017) - Jacobson, Denise L.; Stephensen, Charles B.; Miller, Tracie L.; Patel, Kunjal; Chen, Janet S.; Van Dyke, Russell B.; Mirza, Ayesha; Schuster, Gertrud U.; Hazra, Rohan; Ellis, Angela; Brummel, Sean S.; Geffner, Mitchell E.; et al.
Abstract : Background: Perinatally HIV-infected (PHIV) children have, on average, lower bone mineral density (BMD) than perinatally HIV-exposed uninfected (PHEU) and healthy children. Low 25-hydroxy vitamin D [25(OH)D] and elevated parathyroid hormone (PTH) concentrations may lead to suboptimal bone accrual. Methods: PHIV and PHEU children in the Pediatric HIV/AIDS Cohort Study had total body (TB) and lumbar spine (LS) BMD and bone mineral content (BMC) measured by dual-energy x-ray absorptiometry; BMD z-scores (BMDz) were calculated for age and sex. Low 25(OH)D was defined as ⩽20 ng/mL and high PTH as >65 pg/mL. We fit linear regression models to estimate the average adjusted differences in BMD/BMC by 25(OH)D and PTH status and log binomial models to determine adjusted prevalence ratios of low 25(OH)D and high PTH in PHIV relative to PHEU children. Results: PHIV children (n = 412) were older (13.0 vs. 10.8 years) and more often black (76% vs. 64%) than PHEU (n = 207). Among PHIV, children with low 25(OH)D had lower TB-BMDz [SD, −0.38; 95% confidence interval (CI), −0.60 to −0.16] and TB-BMC (SD, −59.1 g; 95% CI, −108.3 to −9.8); high PTH accompanied by low 25(OH)D was associated with lower TB-BMDz. Among PHEU, children with low 25(OH)D had lower TB-BMDz (SD, −0.34; 95% CI, −0.64 to −0.03). Prevalence of low 25(OH)D was similar by HIV status (adjusted prevalence ratio, 1.00; 95% CI, 0.81 to 1.24). High PTH was 3.17 (95% CI, 1.25 to 8.06) times more likely in PHIV children. Conclusions: PHIV and PHEU children with low 25(OH)D may have lower BMD. Vitamin D supplementation trials during critical periods of bone accrual are needed. Abstract : Supplemental Digital Content is Available in the Text.